The Influence Of Human Resource Information Systems, Training, And Motivation On Employee Performance Through Work Discipline As An Intervening Variable At Pt. Socfin Indonesia (Socfindo) Medan - Indha Aprida Sutari; Yusuf Ronny Edward; Cut Fitri Rostina; syaifuddin syaifuddin (CV. Aksara Global Akademia, 2025)
This study aims to test and analyze the effect of human resource information systems, training, and motivation on employee performance through work discipline as an intervening variable. Employee performance in a company is influenced by several aspects, one of which is the human resource information system, training, motivation and work discipline. Human resource information systems are technological systems that produce information outputs that support reliable decisions and are able to make it easier for workers to complete their responsibilities. Then training is carried out according to the needs of employees balanced by motivation. The discipline aspect also provides important things for success in improving employee performance. The research location is at PT.Socfin Indonesia (Socfindo) Medan located at JL.KL. Yos Sudarso No.106. Medan. Where the linear regression analysis method and sample testing researchers in this study used the slovin formula. As a sample of 150 permanent employees and 30 respondents as validity and reliability tests. The classic assumption test and hypothesis testing (path analysis technique). Based on the results of hypothesis testing in this study, it shows that human resource information systems, training, motivation simultaneously have a positive and significant effect on work discipline. And simultaneously the variables of human resource information systems, training, and motivation have a positive and insignificant effect on employee performance. While work discipline has a positive and significant effect on employee performance. Furthermore, the variables of human resource information systems, training, motivation have a positive and significant effect on employee performance through work discipline as an intervening variable on employees of PT Socfin Indonesia (SOCFINDO) Medan.